2019
DOI: 10.2147/ijn.s192113
|View full text |Cite
|
Sign up to set email alerts
|

<p>Targeted lipid nanoparticle delivery of calcitriol to human monocyte-derived macrophages in vitro and in vivo: investigation of the anti-inflammatory effects of calcitriol</p>

Abstract: Background: Vitamin D 3 possesses anti-inflammatory and modulatory properties in addition to its role in calcium and phosphate homeostasis. Upon activation, macrophages (M) can initiate and sustain pro-inflammatory cytokine production in inflammatory disorders and play a pathogenic role in certain cancers. Purpose: The main purpose of this study was to encapsulate and specifically target calcitriol to macrophages and investigate the anti-inflammatory properties of calcitriol in vitro and in vivo. Methods: In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…As an alternative to target dexamethasone to macrophages, Rafique et al [ 322 ] strengthened the anti-inflammatory effect of another steroid, calcitriol (vitamin D) on human monocytes in vitro using CD163-targeted pegylated nanoparticles loaded with calcitriol. M-CSF/ Granulocyte-macrophage colony-stimulating factor (GM-CSF) differentiated human macrophages from buffy coats were incubated with either non-targeted stealth calcitriol liposomes or stealth liposomes with CD163-antibody or control IgG for 24 h before induction of inflammation by LPS for 4 h. The CD163-targeted calcitriol treatment reduced the mRNA expression of anti-inflammatory markers and increased the expression of the pro-inflammatory cytokine, IL-10.…”
Section: Targeting Cd163 + Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative to target dexamethasone to macrophages, Rafique et al [ 322 ] strengthened the anti-inflammatory effect of another steroid, calcitriol (vitamin D) on human monocytes in vitro using CD163-targeted pegylated nanoparticles loaded with calcitriol. M-CSF/ Granulocyte-macrophage colony-stimulating factor (GM-CSF) differentiated human macrophages from buffy coats were incubated with either non-targeted stealth calcitriol liposomes or stealth liposomes with CD163-antibody or control IgG for 24 h before induction of inflammation by LPS for 4 h. The CD163-targeted calcitriol treatment reduced the mRNA expression of anti-inflammatory markers and increased the expression of the pro-inflammatory cytokine, IL-10.…”
Section: Targeting Cd163 + Macrophagesmentioning
confidence: 99%
“…Therefore, the anti-inflammatory effects may not solely be attributed to the targeting of CD163. Distribution of the liposomes in vivo was investigated using Xenogen in vivo imaging system (IVIS), which revealed accumulation of CD163-targeted liposomes in the liver within 15 min while non-targeted liposomes circulated in the blood stream for more than three and a half hours [ 322 ]. This might indicate that CD163-targeting of calcitriol is favorable and specific as Kupffer cells express CD163.…”
Section: Targeting Cd163 + Macrophagesmentioning
confidence: 99%
“…Rafique et al encapsulated calcitriol into LNPs and developed near-infrared calcitriol PEGylated NPs [PEG-LNP(Cal)] by a microfluidic mixing technique. The results showed that calcitriol can be effectively targeted to macrophages (69). Nanotechnology systems for the targeted delivery of drugs to TAMs are effective methods for mitigating tumor promotion (46).…”
Section: Introductionmentioning
confidence: 99%
“…SPR experiments have been defining in the obtention of decorated liposomes with high affinity to amyloid-β peptide (Gobbi et al, 2010 ; Mourtas et al, 2011 ; Gregori et al, 2017 ), contributing to the development of very promising vectors for the targeted delivery of potential new diagnostic and therapeutic molecules for Alzheimer's disease. SPR sensing based on surface immobilization of the target protein onto Au- CMD chips ( Figure 1E , left) has also contributed to the elucidation of the interplay of decorated liposomes or SLNs and membrane proteins that are overexpressed in malignant tissues (Nielsen et al, 2002 ; Terada et al, 2007 ; Mizrahy et al, 2011 ; Shi et al, 2015a ; Huang et al, 2019 ), in disease-supporting macrophages (Etzerodt et al, 2012 ; Rafique et al, 2019 ) or in T-cells involved in autoimmune diseases (Ding et al, 2015 ). Moreover, SPR studies based on immobilized liposomes ( Figure 1E , right) have shed light on the complex mechanism for the interaction of lectins with glycoliposomes specially designed to target sugar-binding proteins (Tamiaki et al, 2006 ; Sandoval-Altamirano et al, 2017 ).…”
Section: Applications Of Spr-based Biosensors In the Study Of Lnpsmentioning
confidence: 99%